Retraction: Setoguchi et al. Accuracy Assessment of Implant Placement in a Newly Developed Dynamic Navigation System: A Pilot Study. Appl. Sci. 2021, 11, 6593 - Tomoyuki Setoguchi (MDPI AG, 2021)
The published article [...]